Effectiveness of Physical Education, Sports and Health Learning in Elementary Schools - Gaol, Areslon Lumban; Susilawati, Dewi (Sains Global Institut, Indonesia, 2024)
This research aims to determine the process of implementing learning physical education, sports and health at SD Rachmani, sub-district East Karawang, Karawang district. The problem of this research is to know how the process of implementing physical education learning is carried out in sports and health which takes place at SD Rachmani Karawang. This research is a qualitative descriptive research, which describes how implementation of physical education, sports and health learning at SD Rachmani Karawang, the subjects in this study were 4 students, 1 physical education teacher, and 1 head school. The data collection techniques used in this research are observations, interviews, and documentation. Data analysis techniques used in this research are data reduction and data display techniques. Research result shows that the implementation of physical education, sports and health in SD Rachmani Karawang in terms of preparation is quite good, while the implementation and evaluation stages are still not good, apart from that School facilities and infrastructure are incomplete to fulfil the process learning physical education, sports and health, therefore physical education, sports and health teachers are not graduates Professional teachers of physical education, sports and health must further develop their knowledge learning physical education, sports and health.